KEPEMIMPINAN SPRITUAL - Alimuddin Alimuddin (Kelola: Journal of Islamic Education Management, 2019)
Leadership is a subject that is always interesting to continue to study because it has an important role in the organization. Likewise with spiritual leadership as a model of leadership. The purpose of this study is to explain the concept of spiritual leadership as a model of leadership. This type of research is a literature study (Library Research). Spiritual leadership is leadership inspired by belief in God. The leader does not see his position as the highest position so that he requires excelent service from his subordinates, but sees him as a mandate (khalifah) to serve, process, and manage his subordinates so that they can collectively achieve success. Spiritual leadership has the character of true honesty, fairness, focus on righteous deeds, hate formality and organized religion, work more efficiently with less talk and more relaxed, openness to accept change, leaders who are loved and certainly love those they lead and have humility.